TERRESTRIAL VERTEBRATES IN MIS 6 TO MIS 5 DEPOSITS OF THE ZANNONA QUARRY (FAENZA, ITALY) - Rubinato, Giada; Sami, Marco; Fanti, Federico; Marabini, Stefano; Sala, Benedetto; Vai, Gian Battista (Alpine and Mediterranean Quaternary, 2013)
We report few vertebrate remains from the Middle-Upper Pleistocene continental deposits of the Zannona quarry (Faenza, Italy), including two incomplete upper dental series of Stephanorhinus hemitoechus, a frontal with antlers of a cervid, and a fragmentary left scapula of an equid. This material provides additional information on the poorly known terrestrial faunal assemblages of the Quaternary deposits in the Romagna Apennine foothills. Data presented here are discussed within the framework of the well documented stratigraphic transition between the MIS (Marine Isotope Stage) 6 and 5 and support the role of vertebrate continental fauna in the correlation between marine and non-marine successions.